Mikroenkapsulasi Minyak Atsiri Dari Tanaman Nilam (Pogostemon cablin Benth) Sebagai Antijamur Candida albicans - Risnawaty, Risnawaty; Nurliana, Laily; Kurniawati, Desy (Indonesian Journal of Chemical Research, 2017)
Microencapsulation of essential oils from nilam plants (Pogostemon cablin Benth) for antifungal of Candida albicans was carried out. The aims of this study were to know of chemical components, characteristics, and activity test of nilam plants as well as the result test of microencaptulation as antifungal of C. albicans. Nilam essential oils was obtained by using water-vapor destilation with the rendament of 0.88%. Charateristics of nilam essential oils obtained produced are density of 0.947 mg/L, refractive index of 1.506, acid number of 1.122, and dissolved in alcohol 70 and 90% has conducted by Indonesia National Standar. Microencapsulation of nilam essential oils by using spray drying method with the various of the wrapper material of nilam essential oils:maltodextrin (1:12;1:10;1:8) produced solid powders with sticky texture and creamy which giving a spesific aroma of nilam oils. The activity test of antifungal of C. albicans test on liquid essential oil any diffence significantly each various of concentration of 12,5; 25; 50; and 100%. The activity of microcapsule showed that the difference specifically on various of concentrations of 1:12; 1:10 and 1:8 with the good activity power is composition of 1:12. Activity test result showed is any difference significantly between nilam oils and microcapsule.